Description of School-Age Children's Knowledge about Tuberculosis - Yanti, Ni Luh Putu Eva (Indonesian Journal of Global Health Research, 2024)
Tuberculosis in children cases continues to increase. School-age children are a risk group for contracting tuberculosis from family and school. The study aimed to describe school children's knowledge about tuberculosis and its prevention. This research uses a descriptive quantitative research method using a cross-sectional approach. The sampling technique was purposive sampling with 53 respondents. The results showed that students' knowledge about tuberculosis was 58,5% in the good category. Students' knowledge about tuberculosis was still lacking in terms of the symptoms of tuberculosis and tuberculosis treatment. Students did not know about the symptoms of tuberculosis when their weight did not increase for several months. Students did not know the treatment of tuberculosis for six months. Students' knowledge of tuberculosis is good but needs improvement in knowledge of symptoms, transmission, and treatment. Suggestions can be given through health education for school children.